Behavior Disorders in Early Childhood and Maternal Anemia History: A Cross-Sectional Study in Indonesia - Dewi, Noviana; Awanis, Almas; Astriyana, Sevy; Musslifah, Anniez Rachmawati (Journal of Applied Nursing and Health, 2025)
Background: Anemia is a health condition caused by genetic factors, infectious disorders, and the environment. Lead exposure increased the risk of anemia, with several sources including cigarette smoke, motor vehicle exhaust, pesticide residues, and contamination from synthetic textile dyes. Mothers with anemia frequently give birth to children who also experience the same condition, thereby disrupting growth and development and causing behavioral disorders. Therefore, this study aimed to examine the relationship between maternal anemia and behavioral disorders in early childhood in areas with high lead exposure. Methods: A cross-sectional analysis was conducted, and samples were selected using purposive non-random sampling. This study included 16 early childhood education (PAUD) students, 16 parents, and 4 PAUD teachers. Data analysis included descriptive and correlational analyses using SPSS 23. Results: The results showed a correlation between maternal hemoglobin levels and emotional and behavioral disorder scores (-0.508, p < 0.05), as well as autism risk detection (-0.610, p < 0.05). There was also a correlation between the pre-screening child development questionnaire and autism risk detection scores (-0.525, p <0.05).. Conclusion: Mothers with anemia tend to give birth to children who also develop the same condition. The condition disrupts growth and development in children, contributing to behavior disorders.